Abiotic variables in littoral-limnetic gradient of an oxbow lake of Mogi-Guaçu River floodplain, Southeastern, Brazil - Taniguchi,Glória Massae (2004)
The present study aimed to analyse the abiotic characteristics spatial variability in the littoral-limnetic gradient of the Diogo Pond, Mogi-Guaçu River floodplain, as well as evaluating the hydrological influence on the spatial gradient. During the hydrological cycle, four field trips (high water, flood, low water, and drought) were carried out at three sampling stations: littoral, interface, and limnetic region. Analysis of physical and chemical variables allowed to conclude that the time scale established by the hydrological cycle was the main forcing function over the limnological variability of the Diogo Pond. The relative spatial scale related to littoral-limnetic gradient contributed secondarily to the abiotic variability. Littoral was characterized as a distinct compartment from the other stations during the entire hydrological cycle.